The status of the American bollworm, Heliothis armigera (Hubner) (Lepidoptera : Noctuidae), on sunflower in the central Transvaal - Von Maltitz, Emil Friedrich (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1992)
Sunflower production in South Africa has increased four fold since the 1970's. This study was done to elucidate the pest status of Heliothis armigera (Hiibner) on sunflower. Field studies were undertaken at Warmbaths, Brits and Delmas during the summer seasons of 1988/89 to 1990/91. The infestations at the latter two areas were negligible throughout the study period and their statistics have not been included in this thesis. Plant development and oviposition by natural H. armigera populations were found to be correlated as, regardless of planting date, oviposition started at six to seven weeks after planting; when the flowering stage began. A peak in egg numbers was reached by the tenth week with an average for the three seasons at two eggs per plant. The eggs were laid singly on the bracts and bases of the flower buds. A peak in larval numbers was reached at the thirteenth week after planting with the average for the three seasons of 0,4 larvae per plant. The preferred feeding sites were on, between and under the bracts from where the larvae burrow into the pithy tissue of the receptacle. Only six percent of the larvae were found feeding directly on the achenes. Eggs and larvae collected were reared to determine the degree of parasitism. Overall, 19% of the eggs were parasitised; 18% by Telenomus ullyetti Nixon (Scelionidae) and one percent by Trichogrammatoidea lutea (Trichogrammatidae). Larval parasitism at Warmbaths was 23% in 1988/89, 27% in 1989/90 and 34% in 1990/91. Of the parasitised larvae, 44% succumbed to Palexorista prob. laxa (Tachinidae). The remainder were unidentified Braconidae and Ichneumonidae. Predators, such as chrysopids, were observed during the study but their effect on egg and larvae numbers was not studied in detail. A polyhedral virus occurred late in the seasons and caused mortality of the larvae. The low numbers of H. armigera on sunflower, the slight damage to the crop and the reasonably high rate of parasitism, all seem to indicate that H. armigera is not an economica1ly important pest of sunflower and that additional control methods are not justified.
Keywords: Helicoverpa armigera; Noctuidae -- South Africa -- Transvaal; Noctuidae; Sunflowers -- Diseases and pests